Contagious Bovine Pleuropneumonia: A Comprehensive Overview. Issue 4 (July 2020) - Di Teodoro, Giovanni; Marruchella, Giuseppe; Di Provvido, Andrea; D'Angelo, Anna Rita; Orsini, Gianluca; Di Giuseppe, Paola; Sacchini, Flavio; Scacchia, Massimo
Contagious bovine pleuropneumonia (CBPP) is a respiratory disease of cattle that is listed as notifiable by the World Organization for Animal Health. It is endemic in sub-Saharan Africa and causes important productivity losses due to the high mortality and morbidity rates. CBPP is caused by Mycoplasma mycoides subsp. mycoides ( Mmm ) and is characterized by severe fibrinous bronchopneumonia and pleural effusion during the acute to subacute stages and by pulmonary sequestra in chronic cases. Additional lesions can be detected in the kidneys and in the carpal and tarsal joints of calves. Mmm infection occurs through the inhalation of infected aerosol droplets. After the colonization of bronchioles and alveoli, Mmm invades blood and lymphatic vessels and causes vasculitis. Moreover, Mmm can be occasionally demonstrated in blood and in a variety of other tissues. In the lung, Mmm antigen is commonly detected on bronchiolar and alveolar epithelial cells, in lung phagocytic cells, within the wall of blood and lymphatic vessels, inside necrotic areas, and within tertiary lymphoid follicles. Mmm antigen can also be present in the cytoplasm of macrophages within lymph node sinuses, in the germinal center of lymphoid follicles, in glomerular endothelial cells, and in renal tubules. A complete pathological examination is of great value for a rapid presumptive diagnosis, but laboratory investigations are mandatory for definitive diagnosis. The purpose of this review is to describe the main features of CBPP including the causative agent, history, geographic distribution, epidemiology, clinical course, diagnosis, and control. A special focus is placed on gross and microscopic lesions in order to familiarize veterinarians with the pathology and pathogenesis of CBPP.